Popular National Development and the Question of Social Justice (Damascus University Journal of arts and humanities sciences, 2021)
Contemporary underdevelopment is characterized by binary underdevelopment i. e: technological and structural ones. Thus, development, as a necessary medicine for underdevelopment, is not of the nationality of capitalist development with a liberal background or socialist development with Marxist background that collapsed at the end of the 20thcentury. Theological consequence is that the development that is qualified to confront the underdevelopment of the South States is the national popular development, as a mode of development concerned, simultaneously, with the task of capitalist identity and other tasks of a popular nature.The popular national development, which is concerned with the development of the productive forces, is concerned too with building the relations of production with a public identity, primarily. Thus, social justice is the most important question of this type of development, as long as it is being built, to some extent, with the help of labor power of the public. This necessarily requires employment, a condition for absorbing as many proletariat as possible, and a mechanism for fair redistribution of income that ensures the rise of the standard of living of these people to the level required to invest their full capacity in production.Employment, as a mechanism of such importance, has fundamental conditions, of which expanding the national economy in all directions is the most important one, in addition to the adoption of the labor-intensive technology rather than the science- intensive technology or capital-intensive technology.
Keywords: : popular national development; social justice; disengagement; Keynesian; Appropriate technology; labor-intensive technology; science; intensive technology; capital